Seeding Event: - Gaëtan Mourmant (Grounded Theory Review: An International Journal)
This paper addresses the question of initiating, fostering and growing a vibrant economy by developing Spaces of Entrepreneurial Freedom (SoEF). Establishing and developing the SoEF is explained by a seeding event which is the core category of this grounded theory. In short, a seeding event leads to the patching of a potential, structural “hole”, which may prove valuable to an entrepreneurial network. Seeding events are started by an initiator who will recognize a network opportunity and exploit it. After event designing, the initiators implement the event through bold experimentation and using an adaptive structure. If the event is considered successful, the next stages are refining, growing, templating and finally replicating; these stages may occur one after the other or simultaneously. Through the development of SoEF, we suggest that entrepreneurs, governments, universities, large companies, and other players in the business world can improve the development of entrepreneurship at their respective levels.